2010
DOI: 10.1159/000316179
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Management of Psoriasis with Nail Involvement: A Focus on Biologic Therapy

Abstract: Nail involvement in psoriasis is typically overlooked, although it can affect up to 50% of patients with psoriasis and cause functional impact as well as psychological stress that can significantly affect quality of life. In addition, psoriatic patients with nail disease tend to have a more severe skin condition, a higher rate of unremitting and progressive arthritis and more associated anxiety and depression. Historically, the treatment of nail psoriasis has proven difficult, with most patients feeling that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 105 publications
3
49
0
2
Order By: Relevance
“…Enthesitis and dactylitis, important distinguishing features of PsA in many patients, are associated with more severe disease; both can be difficult to treat and can lead to disability [5,13,31]. Approximately twice as many patients with PsA (21%) had nail involvement compared with patients with psoriasis alone (11%), and 44% of patients with PsA reported scalp involvement; however, overall these rates are lower than those previously reported [8,17,18,21,26]. The presence of skin disease in these areas has been found to have a disproportionate effect on QoL and is often difficult to treat, with limited effective treatment options [7,9,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Enthesitis and dactylitis, important distinguishing features of PsA in many patients, are associated with more severe disease; both can be difficult to treat and can lead to disability [5,13,31]. Approximately twice as many patients with PsA (21%) had nail involvement compared with patients with psoriasis alone (11%), and 44% of patients with PsA reported scalp involvement; however, overall these rates are lower than those previously reported [8,17,18,21,26]. The presence of skin disease in these areas has been found to have a disproportionate effect on QoL and is often difficult to treat, with limited effective treatment options [7,9,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the researchers have reported that the frequency of nail involvement in psoriatic patients is about 75–83% [2,6,7,8,16], although there are reports asserting that it is between 10 and 55% [1,3,4,5,9,11]. Moreover, there are reports mentioning that 80–90% of the psoriatic patients will develop nail psoriasis at some point of their lives [1,9,11,12]. Isolated nail psoriasis, without any skin or joint manifestation, is observed in only 1–10% of the patients [3,8,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Nail psoriasis occurrence considerably varies and ranges between 10 and 90% [1,2,3,4,5,6,7,8,9,10,11]. Additionally, it is reported that 80–90% of patients with psoriasis will develop nail psoriasis at some point of their lives [1,2,11,12]. Rarely, isolated nail psoriasis can be observed, but only in 1–10% of patients with psoriasis [3,8,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] [3] There is no sex predilection. Patients above 40 years of age are affected twice as often as those under 20 years.…”
Section: Introductionmentioning
confidence: 99%